LB02.07: EFFECT OF ACUTE DA2 DOPAMINERGIC RECEPTOR BLOCKADE ON PERFORMANCE OF ADRENAL VEIN SAMPLING FOR SUBTYPING OF PRIMARY ALDOSTERONISM. (June 2015) - Rossitto, G.; Battistel, M.; Barbiero, G.; Maiolino, G.; Seccia, T.M.; Bisogni, V.; Mareso, S.; Azzolini, M.; Miotto, D.; Plebani, M.; Rossi, G.P.
Abstract : Objective: As dopamine tonically inhibits aldosterone release via DA2 receptors, we hypothesized that acute DA2 blockade during adrenal vein sampling (AVS) might improve the assessment of lateralization of aldosterone excess in the subtyping of primary aldosteronism. Design and method: we prospectively investigated the acute effect of metoclopramide on the lateralization index [LI, defined as the ratio of aldosterone over cortisol plasma concentration (PAC:PCC) in the dominant over the PAC:PCC in the contralateral side] and on the relative aldosterone secretion index in adrenal vein blood [RI, defined as the ratio of plasma aldosterone concentration (PAC) in the adrenal vein over PAC in inferior vena cava (IVC), normalized by the ipsilateral Selectivity Index]. To this end we compared baseline and post-metoclopramide LI and RI values in 92 consecutive patients undergoing AVS from 2008 to 2014. As gold standard we used the diagnosis of aldosterone-producing adenoma (APA), based on pathology and follow-up data according to the four corners criteria. Results: Metoclopramide increased aldosterone in the IVC and in adrenal vein blood of both sides (p < 0.0001 for all). Even though post-metoclopramide LI provided an accurate identification of APA (AUC = 0.880, p = 0.0001 vs identity line; Youden Index >2.7, sensitivity 81%, specificity 83%), it showed no incremental diagnostic gain over baseline LI (p = 0.75 for ROC curves comparison). Metoclopramide also increased the RI (p < 0.001) both from the dominant and the non-dominant side [3.13 (2.53–4.33) to 8.76 (5.31–12.21); 0.91 (0.68–1.36) to 2.19 (1.61–3.23), respectively]. However, metoclopramide raised the RI on the APA side to values > 1.00 in all the 39 unequivocally diagnosed APA patients. Therefore, a post metoclopramide cut-off for the RI < 1.00 offered 100% specificity in excluding an APA on that side. Conclusions: acute DA2 antagonism exerts a prominent secretagogue effect on aldosterone, but due to a proportionally similar effect on the RI of both sides it did not increase the LI. However, it can increase the specificity of the RI for excluding an APA. This finding might be of particular diagnostic value for AVS studies that are not bilaterally selective.